Rewiring remote urban futures? Youth well-being in northern industry towns - Florian Stammler (Arctic Centre, University of Lapland); Ria-Maria Adams (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Aytalina Ivanova (Arctic Centre, University of Lapland) (Journal of Youth Studies, 2022)
The abstract is available here: https://uscholar.univie.ac.at/o:2112378 The abstract is available here: https://uscholar.univie.ac.at/o:2112378